2010
DOI: 10.1029/2009jb006383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clay content and mineralogy on frictional sliding behavior of simulated gouges: Binary and ternary mixtures of quartz, illite, and montmorillonite

Abstract: [1] We investigated the frictional sliding behavior of simulated quartz-clay gouges under stress conditions relevant to seismogenic depths. Conventional triaxial compression tests were conducted at 40 MPa effective normal stress on saturated saw cut samples containing binary and ternary mixtures of quartz, montmorillonite, and illite. In all cases, frictional strengths of mixtures fall between the end-members of pure quartz (strongest) and clay (weakest). The overall trend was a decrease in strength with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
350
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(412 citation statements)
references
References 44 publications
60
350
2
Order By: Relevance
“…Application of equations (3) and (4) assumes a full (laterally unconstrained) split cylinder sample assembly configuration with constant inclusion thickness and contact area (Tembe et al, 2010).…”
Section: Deformation Experimentsmentioning
confidence: 99%
“…Application of equations (3) and (4) assumes a full (laterally unconstrained) split cylinder sample assembly configuration with constant inclusion thickness and contact area (Tembe et al, 2010).…”
Section: Deformation Experimentsmentioning
confidence: 99%
“…An example of laboratory data recording the behavior of sheared clayey materials is shown at left from Fig. 3 of Ikari [41]; many other experiments exist [42][43][44][45]. Shear--induced permeability decrease is consistently observed in clayey materials, indicating that though one may accomplish plastically, aseismically, slow--slip regions in such materials [40], the accompanying permeability changes would be deleterious to production goals.…”
Section: Illustration Of Shear--induced Dilationmentioning
confidence: 99%
“…Deformation, in such a case, becomes controlled by the mechanical properties of the clay matrix and the CM. Artificial mixtures of quartz and illite gouge exhibit a gradual but constant decrease of shear strength as a function of illite content (Brown et al, 2003;Tembe et al, 2010). In addition, several experimental works have shown that clay-rich fault rocks have velocity-strengthening properties (e.g., Saffer and Marone, 2003;Ikari et al, 2011).…”
Section: Concentrations Of Graphite and Clay In The Black Shear Zonesmentioning
confidence: 99%
“…A number of experiments quantitatively demonstrate how frictional behavior changes when weak materials such as clay minerals and graphite are included in the samples (Logan and Rauenzahn, 1987;Brown et al, 2003;Takahashi et al, 2007;Crawford et al, 2008;Tembe et al, 2010;Oohashi et al, 2013). Several studies show that as little as~10% of these materials is enough to act as a lubricant (e.g., Collettini et al, 2009;Oohashi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%